Discourse Structure and Language Strategy in Unknown interlocutor "Tor Pak Tor Kham Tidfaidaeng" - ฉัตรไยพฤกษ์, จักริน; บุญวรรณ, เขมฤทัย (FOYER: The Journal of Humanities, Social Sciences, and Education, 2019)
This article aims to study the discourse structure of conversation and analyze the language strategies in conversational discourse in conversations between unrelated conversations in "Tor Pak Tor Kham Tidfaidaeng Program" by collecting data for only 10 conversations with the highest number of visitors. The results of the study found that the discourse structure was 3 parts, included starting conversation by greeting and asking, Content structure by acceptance-inquiry and 2) advertising and the ending structure by Farewell and cutting off the conversation. The language strategy consists of 9 strategies, including 1) modality 2) verbal irony 3) Other-repetition 4) Expansion 5) comparison 6) anticipation 7) using sound -puns 8) Using punch line 9) using pronoun-kinship terms. Using language strategies can create humor or entertain according to the purpose of the program